2021
DOI: 10.1097/bot.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Powder Use in Fractures at High Risk of Surgical Site Infection

Abstract: Objectives: To determine if the use of intrawound vancomycin powder reduces surgical-site infection after open reduction and internal fixation of bicondylar tibial plateau, tibial pilon, and calcaneus fractures. Design: Retrospective analysis. Setting: Level I trauma center. Patients: All fractures operatively treated from January 2011 to February 2015 were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…The evidence to support the use of topical antibiotics to prevent surgical site infections in fracture patients continues to build. [2][3][4] Yet, some concern regarding nephrotoxicity from high-dose topical antibiotics in multiple surgeries persists. The results of this study suggest that, among patients with fractures, cumulative doses of local vancomycin powder do not increase the drug-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence to support the use of topical antibiotics to prevent surgical site infections in fracture patients continues to build. [2][3][4] Yet, some concern regarding nephrotoxicity from high-dose topical antibiotics in multiple surgeries persists. The results of this study suggest that, among patients with fractures, cumulative doses of local vancomycin powder do not increase the drug-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that topical antibiotic powder placed in the surgical incision effectively prevents surgical site infections after fracture fixation surgery. [1][2][3] In contrast to intravenous antibiotics, locally applied antibiotics do not require sufficiently high systemic concentrations or adequate blood supply to reach the target site. Thus, topical antibiotics are believed to deliver higher local concentrations to the region of interest without unnecessary systemic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…This study found a reduction in the infection rate with the use of VP (35 patients) when compared with the control group (548 patients) (0% vs. 10.6%, p = 0.04). Although this falls into the realm of orthopaedic trauma, this is the only other study that looked at some type of foot fracture where VP was applied 45 .…”
Section: Sports—primary and Secondary Aclrmentioning
confidence: 99%
“…Fourteen fracture studies were included, with three RCTs, two prospective observational studies, and nine retrospective studies (Table 2) [50][51][52][53][54][55][56][57][58][59][60][61][62][63]. A total of 4,635 patients were included.…”
Section: Fracture Repairmentioning
confidence: 99%